Social capital and socio-demographic changes: from non-differentiation to multifocalisation - Carmo, R. M.; Santos, S. (Sociologia Ruralis, 2014)
This article examines how different socio-demographic trends interrelate with alterations in the traditional forms of social and interpersonal relationships. We will focus on two Portuguese municipalities using the concept of rural community as an analytic starting point for framing and examining the different dimensions of social capital. The survey's data shows that the generalised nature of mutual knowledge and trust, that used to characterise more traditional communities, tends now to depend on new social categories and groups that live and interact in these places. The study contains a multivariate, multiple correspondence analysis, which shows three different profiles of social capital coexisting in the two areas.